Evidences of non-additive effects of multiple parasitoids on Diatraea saccharalis Fabr. (Lep., Crambidae) populations in sugarcane fields in Brazil - Rossi, M. N. (Blackwell Verlag Gmbh, 2004)
Biological control is a relatively benign method of pest control. However, considerable debate exists over whether multiple natural enemies often interact to produce additive or non-additive effects on their prey or host populations. Based on the large data set stored in the Sao Joao and Barra sugarcane mills (state of São Paulo, Brazil) regarding the programme of biological control of Diatraea saccharalis using the parasitoids Cotesia flavipes and tachinid flies, in the present study the author investigated whether the parasitoids released into sugarcane fields interfered significantly with the rate of parasitized D. saccharalis hosts. The author also observed whether there was an additive effect of releasing C. flavipes and tachinids on the rate of parasitized hosts, and looked for evidence of possible negative effects of the use of multiple parasitoid species in this biological control programme. Results showed that C. flavipes and the tachinids were concomitantly released in the Barra Mill, but not in the Sao Jao Mill. Furthermore, in the Barra Mill there was evidence that the parasitoids interacted because the percentage of parasitism did not increase after the release of either C. flavipes or tachinids. In the Sao Joao Mill, when both parasitoid species were released out of synchrony, both the percentage of parasitism by C. flavipes as well as that of the tachinids increased. When large numbers of tachinids were released in the Barra Mill, they caused a significant lower percentage of parasitism imposed by C. flavipes. The implications of the results as evidence of non-additive effects of C. flavipes plus tachinids on D. saccharalis populations are discussed.
Keywords: Cotesia flavipes; Diatraea saccharalis; biological control; non-additive effect; parasitoid; tachinid flies